Field accuracy of HIV rapid diagnostic tests for blood donors screening, Bukavu, Eastern Democratic Republic of the Congo - Théophile Mitima Kashosi; Céléstin Bisangamo Kyambikwa; Philémon Mbarabara Mulongo; Jean Bisimwa Nachega (Journal of Infection in Developing Countries)
Introduction: Rapid diagnostic tests (RDTs) are widely used for point-of-care. point-of-care diagnosis of HIV infection in resource-limited settings. However, there are no data about their field diagnostic performance in Eastern Democratic Republic of the Congo (DRC), especially in the context of blood banks screening for transfusion safety purpose.